STUDY OF DURABILITY PROPERTIES OF HOLLOW CIRCULAR TUBULAR SECTIONS WITH AND WITHOUT FRP (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The present work deals with the evaluation of both fully and partially concrete filled FRP tubes to attain the durability of the specimens. To achieve this, preliminary tests was done to evaluate the properties of the materials used. From these material properties, mix design has been made. Here, two grades of concrete mixes were used (i.e.; M20 and M25). With these mixes, conventional concrete cylinders were made. After 28 days of curing the axial compressive strength was found out. Fully and partially concrete filled FRP tubes were made with the same concrete mixes. Partially concrete filled FRP tubes have centrally placed PVC pipes with different diameters. After 28 days of curing of concrete filled FRP tubes, durability tests were found out and they were graphically presented from that the compressive strength of the concrete cylinders were reduced.